Gluon gravitational form factors at large momentum transfer - Xuan-Bo Tong (Elsevier, 2021)
We perform a perturbative QCD analysis of the gluonic gravitational form factors (GFFs) of the proton and pion at large momentum transfer. We derive the explicit factorization formula of the GFFs in terms of the distribution amplitudes of hadrons. At the leading power, we find that the gluon GFFs Ag and Cg scale as Agπ(t)=Cgπ(t)∼1/(−t) for pion, Agp(t)∼1/(−t)2 and Cgp(t)∼ln2⁡(−t/Λ2)/(−t)3 for proton, respectively, where t is the momentum transfer and Λ a non-perturbative scale to regulate the endpoint singularity in Cgp calculation. Our results provide a unique perspective of the momentum dependence of the GFFs and will help to improve our understanding of the internal pressure distributions of hadrons.